Early life conditions and financial risk-taking in older age - Dimitris Christelis; Loretti I. Dobrescu; Alberto Motta (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
Using life-history survey data from eleven European countries, we investigate whether childhood conditions, such as socioeconomic status, cognitive abilities and health problems influence portfolio choice and risk attitudes later in life. After controlling for the corresponding conditions in adulthood, we find that superior cognitive skills in childhood (especially mathematical abilities) are positively associated with stock and mutual fund ownership. Childhood socioeconomic status, as indicated by the number of rooms and by having at least some books in the house during childhood, is also positively associated with the ownership of stocks, mutual funds and individual retirement accounts, as well as with the willingness to take financial risks. On the other hand, less risky assets like bonds are not affected by early childhood conditions. We find only weak effects of childhood health problems on portfolio choice in adulthood. Finally, favorable childhood conditions affect the transition in and out of risky asset ownership, both by making divesting less likely and by facilitating investing (i.e., transitioning from non-ownership to ownership).
urn:nbn:de:hebis:30:3-241128
Keywords: G11; D14; E21; J13; C23; C25; 330; Portfolio Choice; Childhood; Socioeconomic Status; Cognition; Health; Financial Risk; Anlageverhalten; Risikopräferenz; Erwachsene; Kinder; Sozialer Status; Kognition; Gesundheit; Schätzung; Europa